(untitled) (Journal of the Management Sciences, 2024)
The study addresses the challenges and opportunities attributed to sustainable cooperative entrepreneurship in Anambra State, Nigeria. The objectives are to investigate the economic challenges as it affects the performance of cooperative entrepreneurship and economic impact on the growth of cooperative entrepreneurship in Anambra State. The study is anchored on Stakeholders’ Theory. The study adopted a descriptive survey research design in order to obtain relevant and adequate information from respondents. The population of the study was drawn using simple random sampling from eight local government areas, two each from the agricultural zones of the State and making up of four thousand two hundred and thirty-eight (4,238), while the total sample was 353. Inferential statistics used was multiple regression analysis. The result showed that cooperative entrepreneurship disruption (p= 0.000 < 0.05) and challenges cooperative entrepreneurship (p= 0.000 < 0.05). The study concluded that cooperative entrepreneurship disruption was a driver to entrepreneurial success and entrepreneurial innovation has been a challenge among cooperative societies. The study recommended that cooperatives should strive for larger performance in the face of adversity.